12-Month changes of muscle strength, body composition and physical activity in adults with dystrophinopathies. Issue 10 (8th May 2022) - Jacques, Matthew F.; Onambele-Pearson, Gladys L.; Reeves, Neil D.; Stebbings, Georgina K.; Dawson, Ellen A.; Stockley, Rachel C.; Edwards, Bryn; Morse, Christopher I.
Abstract: Purpose: Muscular dystrophy (MD) is an umbrella term for muscle wasting conditions, for which longitudinal changes in function and body composition are well established in children with Duchenne (DMD), however, changes in adults with DMD and Beckers (BMD), respectively, remain poorly reported. This study aims to assess 12-month changes in lower-limb strength, muscle size, body composition and physical activity in adults with Muscular Dystrophy (MD). Methods: Adult males with Duchenne MD (DMD; N  = 15) and Beckers MD (BMD; N  = 12) were assessed at baseline and 12-months for body composition (Body fat and lean body mass (LBM)), Isometric maximal voluntary contraction (Knee-Extension (KEMVC) and Plantar-Flexion (PFMVC)) and physical activity (tri-axial accelerometry). Results: 12-Month change in strength was found as −19% (PFMVC) and −14% (KEMVC) in DMD. 12-Month change in strength in BMD, although non-significant, was explained by physical activity ( R 2 =0.532–0.585). Changes in LBM (DMD) and body fat (BMD) were both masked by non-significant changes in body mass. Discussion: 12-Month changes in adults with DMD appear consistent with paediatric populations. Physical activity appears important for muscle function maintenance. Specific monitoring of body composition, and potential co-morbidities, within adults with MD is highlighted. Implications for rehabilitation: Quantitative muscle strength assessment shows progressive muscle weakness in adults with Duchenne Muscular Dystrophy is comparable to paediatric reports (−14 to −19%). Physical activity should be encouraged in adults with Beckers Muscular Dystrophy, anything appears better than nothing. Body composition, rather than body mass, should be monitored closely to identify any increase in body fat.